2015
DOI: 10.1007/s11548-015-1250-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient-specific instrument can achieve same accuracy with less resection time than navigation assistance in periacetabular pelvic tumor surgery: a cadaveric study

Abstract: In simulated periacetabular pelvic tumor resections, PSI technique enabled surgeons to reproduce the virtual surgical plan with similar accuracy but with less bone resection time when compared with navigation assistance. Further studies are required to investigate the clinical benefits of PSI technique in pelvic tumor surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
81
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(84 citation statements)
references
References 25 publications
2
81
1
Order By: Relevance
“…Among the previous studies, the only study that presented quantitative measurement of the in vivo accuracy of the navigation system reported an average of 2.5 mm cutting error using the navigation system . A previous study comparing the PSI and the navigation system showed similar accuracy with the 3D‐printed PSI and the navigation system . In addition, the 3D‐printed PS‐BTRG can be duplicated to shape a structural bone allograft, which has remained a challenge when using a navigation system .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Among the previous studies, the only study that presented quantitative measurement of the in vivo accuracy of the navigation system reported an average of 2.5 mm cutting error using the navigation system . A previous study comparing the PSI and the navigation system showed similar accuracy with the 3D‐printed PSI and the navigation system . In addition, the 3D‐printed PS‐BTRG can be duplicated to shape a structural bone allograft, which has remained a challenge when using a navigation system .…”
Section: Discussionmentioning
confidence: 99%
“…Three‐dimensional (3D)–printing technology allows for an advanced approach to limb salvage surgery in both components. In the first step of limb salvage surgery, 3D‐printing technology has been mainly used with the use of a 3D‐printed patient‐specific instrument (PSI) . For the reconstruction of bone defects, 3D‐printing technology has been utilized in manufacturing custom‐made implants, but only a few studies have reported on the surgical outcomes with short‐term follow‐up …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations